Analisis Karakteristik Anak Berkebutuhan Khusus: Autisme Di Flexi School Banda Aceh - Shinta Delfianti; Khalida Ayuni; Alifah Rizki; Hijriati Hijriati (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2024)
Children with special needs are those who have physical, intellectual and social emotional limitations, so they have obstacles in their growth and development process. One of the children with special needs is autism. Autistic children are children who have abnormalities in neurological development that affect their communication and interaction styles with other people and also the things around them. Flexsi School is a school with segregation services, where there are several children with different special needs. In conducting observations the researcher focused on one child with autism, therefore the researcher tried to research this with the aim of finding out what the characteristics of autistic children are. Flexsi School, the characteristics of children with special needs are of course different and diverse, one of which is autism, they have the right to receive education like children in general. Children who experience autism also have a variety of behaviors, each with the same abnormalities. This type of research is descriptive qualitative. The data collection methods used were observation, interviews and documentation. The results of this research show a wide variety of behavior in children with autism, which requires attention from their caregivers. Flexsi school provides good attention and needs to children with special needs.